The functional agrobiodiversity in the Douro demarcated region viticulture: utopia or reality? Arthropods as a case study - A review - Gonçalves, Fátima (2019)
Aiming to reduce the losses of biodiversity and the degradation of associated ecosystem services, the United Nations established the 2011-2020 period as the UN Decade on Biodiversity. During this period, the countries involved compromised on implementing the Strategic Plan for Biodiversity, including the Aichi Biodiversity Targets. The argument is that biological diversity underpins the functioning of ecosystems and the provision of services essential to human well-being, further contributing to economic development and the achievement of the Millennium Development Goals. The purpose of this review is to present results of research and academic works carried out over several years in the Douro Demarcated Region in the field of functional agrobiodiversity, understood as the part of ecosystem biodiversity that provides ecosystem services, which support sustainable agricultural production and can also bring benefits to the regional and global environment and to society as a whole. Such studies specifically aimed to contribute knowledge about the diversity of arthropods in the vineyard ecosystem and about practices that can increase their abundance, diversity and services provided. In this context, a general characterization of the arthropod community identified in the vineyard ecosystem is conducted, complemented by information on the role played, by the taxonomic groups identified. The importance of increasing arthropod populations, the vegetation of vineyard slopes, and the existence of shrubs, forests and hedgerows next to the vineyards is discussed. The fundamental role of soil management practices is also referred, namely that of ground cover and the application of compost from winery wastes in the abundance and diversity of these organisms populations. Finally, bearing in mind the importance of the use of this information by vine growers, the measures taken for its dissemination are also presented